Evaluation of drug promotional brochures in a tertiary teaching hospital of Kannur, India - Ratheesh, R.; Mohandas, Bindu; K., Bhaskaran (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Pharmaceutical industries worldwide are heavily involved in aggressive drug promotions. WHO has framed guidelines for ethical drug promotion in 1988. The transparency of pharmaceutical advertisements is important because decision of the physician is likely to be influenced by the claims made by the pharmaceutical companies in the promotional drug brochures and pharmaceutical industries treat their marketing material as “educational material” for doctors. Authors did this study to analyze the information given on drug promotional brochures by the drug companies using ethical criteria of drug promotion by WHO 1988 and to verify the authenticity of the claims given by the pharmaceutical companies in drug promotional brochures. Methods: Cross sectional study extending from 1/8/2012 to 31/7/2013. 612 drug promotional brochures satisfied our inclusion criteria. Drug brochures were analyzed with WHO ethical criteria 1988 and further categorizing the data into type of claims, number and source of references. Validity of journal articles were checked by using a validity measure developed by Cardarelli. Results: Total 612 brochures satisfied inclusion criteria. INN was mentioned in 93.8% of collected brochures. Brand name was mentioned in 100% brochures. Content of active ingredients was mentioned in 92% of brochures. Name of the other ingredients known to cause problem 28.4% of brochures. Dosage form or regimen was mentioned in 23.2% of brochures. Approved therapeutic use mentioned in 65.7% brochures. Side effects and major adverse drug reactions were mentioned in 31.4% brochures. Precautions and contraindications and warnings were mentioned in 30.4% drug promotional brochures. Drug interactions were mentioned in 26.5% brochures. Name and address was mentioned by 69.1% brochures. There were 1144 claims and 739 references. Efficacy claims were 84.88% of the total claims. Main source of reference was from journal articles (74.1%) and among them 49.65% were randomized control trials. Only 47.94 % of the journal references were valid. Conclusions: Brochures were lacking in vital information which included contraindication, warning, precaution, name of the other ingredients known to cause problem hence companies were found violating WHO ethical criteria. Claims were not well supported with references. Less than half of the given journal references were only valid. This study highlights the need of healthcare professionals to remain cautious about promotional material presented by pharmaceutical representatives.